Registro das memórias: uma questão identitária - Assis, Maria José Paulino De (2015)
This work has the broad objective to investigate theoretical foundations about memories and identities that are supporting the pedagogical intervention project. This intervention aims to record the memories and its contribution to the community, from the design to recover the past and tradition is a way to give meaning to their own existence through the discovery identity. We show the methodology of the practical application of the intervention design and the analysis of textual productions developed in the classroom with students from 9th grade of elementary school. The theoretical support of this research is based on Bergamaschi (2002) Memory: between the oral and the written, Hall (2011), Cultural identity in postmodernity, Le Goff (2013) History and Memory, Matos (2014) The word of the storyteller: his educational dimension in contemporary times, Schnneuwly; Dolz (2011) Genres oral and written texts in school and has support from the works of Casimiro de Abreu (1999); Manuel Bandeira (2004); Cecilia Meireles (2004); José Lins do Rego (2008), among others. From this study was drawn up intervention project that provides a record of personal and family memories, starting from speaking, as a team, for writing mode. The exercise of orality first occurs spontaneously and disengaged, without formal concern, then is recorded on video. Motivating texts are presented, especially the novel Menino de Engenho (Plantation Boy), by José Lins do Rego, in which the protagonist narrates situations with family, exposing the respect, admiration and the delight of the affectionate familiarity, still exposes the storytelling marked its childhood. The writing activity takes place in order to record data about the life of each one, from birth to the present day, and your social life, thus creating a report of memories. Another time are narrated events lived with relatives - parents, siblings, cousins, grandparents, uncles ... - significant for your memories and identity formation. The corpus analysis of the research made it possible to prove that the proposed objective was achieved.